Delayed onset bleed after percutaneous kidney biopsy: is it the same as early bleed?. (February 2022) - Bhadauria, Dharmendra; Jose, Leena; Kushwaha, Ravi; Kaul, Anupma; Nandan, Raghu; Singh, Vivek; Prasad, Narayan
Background: While the majority of bleeding complications after a percutaneous kidney biopsy (PKB) occur early (≤24 h), delayed onset bleeding complications (>24 h) have been rarely reported and can be catastrophic for the patient. Purpose: To describe the incidence, risk factors, and outcomes of delayed bleeding complications after PKB. Material and Methods: We retrospectively studied native and graft kidney biopsies in patients who developed delayed bleeding complications (>24 h) after the biopsy performed in the Department of Nephrology and Renal Transplantation of a tertiary care medical institution in north India between January 2014 to December 2018. Results: Of the 4912 renal biopsies reviewed, 20 patients (16 men, 4 women; 0.40%) had a delayed biopsy bleeding complication. Of these patients, 95% had major bleeding complications requiring blood transfusions and 85% needed intervention like gelfoam/coil embolization. Despite intervention, one patient (5%) had mortality due to complications of bleeding and sepsis. When compared to a control group of patients with early biopsy bleed, patients with the delayed biopsy bleed had similar demographic and clinical profiles except for higher pre-biopsy hemoglobin and lower systolic and diastolic blood pressure. Conclusion: A post-PKB delayed onset bleed is not uncommon, and the vast majority of these patients had major bleeding complications requiring blood transfusions and/or intervention like embolization. They had a similar demographic and clinical profile presentation as early bleed patients. Meticulous outpatient monitoring and patient education after discharge may be useful to detect this complication promptly and to intervene early to have good patient outcome.